Impact of COVID-19 Pandemic on Consumption of Anxiolytics, Antipsychotics, and Antidepressants in South Italian Region - Vittoria Satriani; Emanuela Santoro; Mario Capunzo; Rosaria Flora Ferrara; Roberta Manente; Biagio Santella; Gianluigi Franci; Francesco De Caro; Giovanni Boccia (Life)
The COVID-19 lockdown had significant consequences on the mental health of millions of people, leading to the increasing prescription and use of psychotropic drugs. Due to the lack of data in the current literature, this study aims to estimate the trends in the consumption of anxiolytics, antipsychotics, and antidepressants before and during the pandemic on people in the South Italian region. We conducted a retrospective observational study, retrieving prescriptions of anxiolytics, antipsychotics, and antidepressants dispensed in pharmacies of the Basilicata region (South Italy) for the period 2019–2021. We presented the data, expressed in Daily Defined Doses (DDDs) for 1000 persons/day (DHD), on a total resident population of 95,021, dividing the age groups into categories <30, 30–50, 50–70, and >70 years. We conducted a linear regression model to examinate consumption trends across years. Software XLSTAT was used for statistical analysis. During the study period, more than 85,000 boxes of psychotropic medications were dispensed. The research showed an increase in the sales of all three categories of drugs examined, with a greater rise in benzodiazepines (88.5%) and selective serotonin reuptake inhibitors (81.9%) in 2021 compared to 2019, especially among women under 30 years. The COVID-19 pandemic had led to an increase in the consumption of psychotropic drugs, confirming the significant impact on the population’s mental health.